Pengembangan Bahan Ajar Interaktif Flipbook Berbasis Literasi Sains untuk Melatih Keterampilan Berpikir Kritis Siswa pada Kurikulum Merdeka - Aria, Rizki; Liani, Novi Sari; Rahmi, Rahmi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Independent Curriculum emphasizes strengthening 21st-century skills, particularly scientific literacy and critical thinking. However, these skills still need to be improved in students. This study aims to analyze the feasibility and effectiveness of interactive flipbook learning materials based on scientific literacy in improving students' critical thinking skills. The research method used was the Four-D development model: Define, Design, Develop, and Disseminate. Validation results showed that the flipbook learning materials received an excellent rating in the aspects of content, presentation, graphics, language, and learning design, with an overall average percentage of 91.57%. Media trials indicated that the learning materials were suitable for use at the individual, small group, and field levels, without requiring additional revisions. These findings confirm that scientific literacy-based flipbooks are not only feasible but also effective in training students' critical thinking skills, while increasing interest and engagement in learning.